Pyrolysis for Biochar Purposes: A Review to Establish Current Knowledge Gaps and Research Needs - MANYA, Joan J (Environmental science & technology, 2012)
According to the International Biochar Initiative (IBI), biochar is a charcoal which can be applied to soil for both agricultural and environmental gains. Biochar technology seems to have a very promising future. Nevertheless, the further development of this technology requires continuing research. The present paper provides an updated review on two subjects: the available alternatives to produce biochar from a biomass feedstock and the effect of biochar addition to agricultural soils on soil properties and fertility. A high number of previous studies have highlighted the benefit of using biochar in terms of mitigating global warning (through carbon sequestration) and as a strategy to manage soil processes and functions. Nevertheless, the relationship between biochar properties (mainly physical properties and chemical functionalities on surface) and its applicability as a soil amendment is still unclear and does not allow the establishment of the appropriate process conditions to produce a biochar with desired characteristics. For this reason, the need of enhancing the collaboration among researchers working in different fields of study is highlighted: production and characterization of biochar on one hand, and on the other measurement of both environmental and agronomical benefits linked to the addition of biochar to agricultural soils. In this sense, when experimental results concerning the effect of the addition of biochar to a given soil on crop yields and/or soil properties are published, details regarding the properties of the used biochar should be well reported. The inclusion of this valuable information seems to be essential in order to establish the appropriate process conditions to produce a biochar with more suitable characteristics.